(untitled) (Baghdad Science Journal, 2010)
The study was conducted during spring seasons of 2000 and 2001.The aim was to study the changes in the moisture content of sunflower plants during growth stages under hardening conditions to drought tolerance .Agricultural practices were made according to recommendation. Asplit-split plots design was used with three replications. The main plots included irrigation treatments:irrigation to100%(full irrigation),75and50%of available water. The sub plots were the cultivars Euroflor and Flame.The sub-sub plots represented four seed soaking treatments: Control (unsoaked), soaking in water ,Paclobutrazol solution(250ppm),and Pix solution(500ppm). The soaking continued for 24 hours then seeds were dried at room temperature until they regained their original weight. Amount of water for each irrigation were calculated to satisfy water depletion in soil using a neutron meter. Results indicated that plant moisture content was not affected by irrigation treatments in both seasons and as a mean of seasons ,except after 72 days from planting in the season 2000.when stress 800 Kp caused a decreased in moisture content by 4.55and 5.18% compared with full irrigation and stress 600 Kp, respectively. Euroflor was superior over Flame after 30 days from planting by 13.64% in the season of 2000 and by 6.23% as a mean of seasons , and by 2.80% after 86 days from planting in the season of 2001.While Flame was superior by 2.75% after 58 days from planting in the season of 2001. Soaking in water , paclobutrazol and pix solutions increased plant moisture content by 4.56,3.92 and 3.82% after 86 days from planting in the season 2000 , soaking in water and paclobutrazol solution increased plant moisture content by 2.61 and 2.62% as amean of seasons compared with unsoaked treatment. In conclusion, soaking the seeds presowing in water or plant growth regulators could improve water relations of plants , and increase moisture content in plants tissues especially during flowering and seed filling , when the water requirements increased and associated with high temperature in spring season in Iraq.